Adverse prognosis of patients with septal substrate after VT ablation due to electrical storm - Müller, Julian; Chakarov, Ivaylo; Halbfass, Philipp; Nentwich, Karin; Ene, Elena; Berkovitz, Artur; Sonne, Kai; Barth, Sebastian; Waechter, Christian; Behnes, Michael; Akın, Ibrahim; Fodor, Stefan; et al. (JACC Clinical electrophysiology, 2023)
Background - Data about ventricular tachycardia (VT) ablation in patients with electrical storm (ES) is limited. - Objectives - This study sought to compare the prognostic outcome of patients undergoing VT ablation after ES with and without a septal substrate. - Methods - In this large single-center study, consecutive patients presenting with ES and undergoing VT ablation from June 2018 to April 2021 were included. Patients with septal substrate were compared with patients without septal substrate regarding endpoints of cardiovascular mortality, VT recurrences, recurrences of the clinical VT, and rehospitalization rates. - Results - A total of 107 patients undergoing a first VT ablation because of electrical storm (ES) were included (age 65 ± 13 years, 86% male, 45% ischemic cardiomyopathy). Major complications occurred in 11% of all patients with increased postinterventional third-degree atrioventricular blocks among patients with septal substrate (9% vs 0%; P = 0.063). Partial ablation successes were similar (95% with a septal substrate vs 100% without a septal substrate; P = 0.251). Complete ablation success was achieved in 63% with a septal substrate and in 87% without a septal substrate (P = 0.004). After a median 22 months of follow-up, patients with septal substrate died significantly more often from cardiovascular causes (26% vs 7%; log-rank P = 0.018). In univariate analysis cardiovascular mortality for ES patients with septal substrate was 4.1-fold higher (HR: 4.192; CI: 1.194-14.719; P = 0.025). Independent predictors of adverse outcome in multivariable regression analysis were presence of septal substrate (HR: 5.723; P = 0.025) and increased age (HR: 1.104; P = 0.003). Recurrences of any ventricular arrhythmia (67% vs 56%; log rank P = 0.554) and rehospitalization rates (80% vs 66%; log rank P = 0.515) were similar between groups. Recurrences of clinical VT were similar (7% vs 2%; P = 0.252). - Conclusions - Presence of a septal substrate is associated with adverse long-term cardiovascular mortality in patients admitted for VT ablation after ES. Despite decreased acute ablation successes in these patients, VT recurrence rates were similar to those without a septal substrate during follow-up.